Vaginal tablets of dequalinium chloride 10 mg versus clotrimazole 100 mg for vaginal candidiasis: a double-blind, randomized study - Manopchai Thamkhantho (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: To compare the clinical response, microscopic examination and fungal culture between dequalinium chloride (DQC) and clotrimazole (CT) for treating vaginal candidiasis (VC). Methods: The double-blind, randomized study was conducted from September 2014 to September 2016 at Siriraj Hospital, Thailand. Eligible participants were Thai women diagnosed with VC by microscopic examination. The exclusion criteria included immunocompromised conditions, consumption of antifungal drugs, and having recurrent VC. Each participant was randomized with a 1:1 allocation to receive six vaginal tablets of 100 mg CT or 10 mg DQC. Two visits included 10 ± 2 days (C1) and 38 ± 4 days (C2). Outcome measures were improvement of VC symptoms, microscopic examination, culture, satisfaction and tolerability. Results: Of 155 eligible participants, 150 were randomized and allocated into CT (N = 76) and DQC (N = 74). The average age was 31.1 ± 7.2 years. Comparable improvement of clinical response was demonstrated (OR at C1 0.79, 95% CI 0.56–1.10, p = 0.197; and OR at C2 0.99, 95% CI 0.69–1.43, p = 0.985). Of CT and DQC groups, the microscopic examination was positive at 11/75 (14.9%) vs 18/72 (25.3%) at C1 and 18/74 (24.3%) vs 28/66 (42.4%) at C2. And the culture was positive at 25/75 (33.8%) vs 46/72 (65.7%) at C1 and at 26/74 (36.6%) vs 46/66 (69.7%) at C2. Most participants had high satisfaction and tolerability and none reported any side effects. Conclusion: DQC and CT show comparable clinical response but CT results in greater improvement of microscopic examination and fungal culture. Clinical trial registration: The Clinical Trial Registry number was NCT02242695. (September 17, 2014).